CREATIVE LAMP MODELS DURING THE MID-AUTUMN STREET FESTIVAL OF TUYEN QUANG - Dương , Xuân Quyền (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2024)
Creating lantern models in the Tuyen Quang Mid-Autumn Festival street festival is an indispensable activity. Here, artisans demonstrate their knowledge and emotions to carry out pre-planned topics. Artisans in the city have discussed and carefully prepared materials and tools to create artistic models. Once we experience the Mid-Autumn Festival street festival, we can clearly see that the artist did not take the topic from somewhere far away, but appeared in literature, in painting... recreating it into a lantern model that attracts all eyes. of attendees in the festival cannot stay away. Artistic elements are basic elements such as; Ideas and materials, model design, decoration and color coordination are skillfully combined by artists. In the Tuyen Quang Mid-Autumn Festival, in addition to traditional models, models with themes from modern society such as Tom and Jerry, Donal the Duck , etc. are included by artisans, creating a difference. Close to domestic and international tourists. Because of them, the familiar image of the place where they lived appeared once again in a strange place. Make people and tourists love traditional and modern cultural values more, consciously preserving them for future generations.